FORENSIC NETWORK ANALYSIS AND IMPLEMENTATION OF SECURITY ATTACKS ON VIRTUAL PRIVATE SERVERS - saragih, Naikson; Panjaitan, Ridho Agus Wery Nanda; Purba, Mufria Jonatan (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
ABSTRACT-PT Kodinglab Integrasi Indonesia's Virtual Private Server (VPS) product requires good quality standards, including security. The challenge that arises is still frequent disruptions to the protection of PT Kodinglab's VPS customers, where it is difficult to identify the source of the attack. Network forensics in the form of dead forensics and live forensics using the NIST method with the stages of collection, examination, Analysis, and reporting are used to find the source of the attack. Data for dead forensics comes from snort tools, and data for live forensics comes from capture Wireshark. The collection stage involves collecting attack data from snort logs and wireshark for life forensics. While the examination dataset stages are further analyzed and mapped. Advanced check on the server via syslog snort. From the attack testing carried out to obtain information in the form of the attacker's IP address, destination IP address, date of the attack, server time, and type of attack from testing the TCP Flooding and UDP Flooding attacks, all attacks on the customer's VPS can be identified. The information obtained regarding the attacker is in the form of the date and time the attack occurred, the attacker's IP address and the victim's IP address, and the protocol used. Kata kunci : Network Forensic, Dead Forensic, Live Forensic, Virtual Private Server, DDos, TCP Flooding, UDP Flooding.